2019
DOI: 10.1029/2018je005847
|View full text |Cite
|
Sign up to set email alerts
|

Annual Cycle of Gravity Wave Activity Derived From a High‐Resolution Martian General Circulation Model

Abstract: The paper presents results of simulations with a high‐resolution (equivalent to ∼67‐km grid size) Martian general circulation model (MGCM) from the surface up to the mesosphere for a full Martian year. The obtained climatology of the small‐scale disturbances can serve as a proxy for gravity waves (GWs) that are largely not resolved by MGCMs with conventional grid resolution and thus have to be parameterized. GW activity varies greatly with season and geographical location, which contradicts with the constant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…The amplitude of density fluctuations steadily grows from ∼5 to 10% (in the average sense) during the southern winter. This is consistent with the recent simulations using a GW-resolving Martian GCM [29], which also demonstrate the increase of GW activity at the southern high-latitudes during the aphelion season. Note that the results of simulations are shown at~80 km, whereas the majority of aerobraking data come from passes with pericenter altitudes between 105 km and 111 km (see red lines in Figure 1A).…”
Section: Gravity Wave Activitysupporting
confidence: 92%
See 1 more Smart Citation
“…The amplitude of density fluctuations steadily grows from ∼5 to 10% (in the average sense) during the southern winter. This is consistent with the recent simulations using a GW-resolving Martian GCM [29], which also demonstrate the increase of GW activity at the southern high-latitudes during the aphelion season. Note that the results of simulations are shown at~80 km, whereas the majority of aerobraking data come from passes with pericenter altitudes between 105 km and 111 km (see red lines in Figure 1A).…”
Section: Gravity Wave Activitysupporting
confidence: 92%
“…Larger-scale background winds strongly influence the vertically propagating harmonics via wave refraction and filtering, thus modulating the spatiotemporal and spectral characteristics of the GW field. Some of these phenomena have been explored in the lower and middle atmosphere using a high-resolution (GW-resolving) Martian general circulation model (MGCM) [27][28][29]. Thus, GW activity in the thermosphere is a complex result of the local wave excitation and processes of wave generation and propagation from below.…”
Section: Introductionmentioning
confidence: 99%
“…Medvedev et al (2015) implemented a nonlinear spectral gravity wave parameterization (Yiǧit & Medvedev, 2010) in their GCM, extended up to 130 km, and their simulations showed that (1) GW decelerate zonal winds at all seasons, (2) they produce jet reversals similar to those observed in the terrestrial mesosphere and lower thermosphere, and (3) GW weaken the meridional wind and modify the zonal mean temperature by up to ±15 K. However, modeling efforts for Mars suffer from lack of measurements to validate predicted wind fields and from no observational constraints on the GW forcing (Creasey et al, 2006a). Other studies performed high‐resolution simulations ( 60 km grid size) with a general circulation model in order to resolve a significant portion of small‐scale GWs and to capture the impact of GWs on the dynamics and energetics of Mars atmosphere without any parameterizations (Kuroda et al, 2015, 2016, 2019). Those authors showed that the GW activity varies greatly with season and geographical location, with stronger wave generation in the northern hemisphere winter in the mesosphere and smaller activity in polar regions of the troposphere throughout all seasons.…”
Section: Introductionmentioning
confidence: 99%
“…The Martian surface is much rougher and near-surface winds are stronger than on Earth. Simulations using Martian GCMs with increased resolution clearly demonstrate enhanced wave activity over mountainous regions [5][6][7][8]. A large bow-shaped stationary GW signature was observed at the cloud tops of Venus [9].…”
Section: Wave Generation and Sources Of Gravity Wavesmentioning
confidence: 93%
“…Weather on Mars, Venus and, especially, Jupiter [15] is more volatile than that on Earth. Simulations with high-resolution GCMs show that the seasonal variations of GW activity both in the lower and upper atmospheres of Mars are tightly linked with the behavior of the circumpolar vortex and its instability, in particular [8].…”
Section: Wave Generation and Sources Of Gravity Wavesmentioning
confidence: 99%